Uma abordagem heurística para o problema de planejamento da produção em fundições - estudo de caso - Wobeto, Edson Inacio (2008)
The main objective of this work is to propose optimization methods of the production to a medium size market foundry industry. Taking into consideration the peculiarities of the enterprise used as case study, on the contrary of many other works in this area, the present research is focused in the production programming which is based in the macharia ( it is a mold made of sand which serves to give shape to the final piece) and molding machines programming. The kilns programming do not represent a delay in the productive process which has been studied, however, their capacity is taken into consideration during the production of the optimization methods. The proposed model considers the programming of tasks in parallel machines with families set up dependent of the sequence. In order to solve the problem it is used a meta-heurística GRASP. The computing results show that it is significantly possible to improve the procedure of the production programming nowadays used in the foundry industry case study.